Formasi Semilir Fasies Formasi Semilir di Daerah Prambanan dan Sekitarnya: fasies formasi semilir - Astuti, Bernadeta Subandini; Isnawan, Dianto (Retii, 2024)
Regionally, the Semilir Formation is composed of volcanic products. That are dominated by tuff and lapilli, deposited in shallow marine to non-marine environments in the early Miocene to Middle Miocene, the deposition continued until the end of the Miocene. Based on outcrops in the Wukirharjo area, Prambanan, the Semilir Formation, is found to have debris flows and slumps, there is no information about these outcrops regionally, and this is the background to the research. The purpose of the study was to describe the character and facies of the Semilir Formation. The method used was stratigraphic measurement accompanied by paleontological analysis. The results of the study, the Semilir Formation can be divided into 2 facies classes, namely facies F (debris flow) and facies C (turbidity current). The lower facies of the debris flow product is 95 meters thick, composed of dominant lapilli-andesite breccia with a sandstone base mass, with a northwest-southeast paleocurrent direction; facies C is a product of current turbidity in the upper part composed of dominant tuff and sandstone-mudstone repetitions, with a west-east paleocurrent direction. The presence of debris flows and slump as the boundary between the two facies, or the beginning of the deposition of turbidity lithology products at this time.The age of the Semilir Formation in the research area using primary data is N6-N9, with a time gap of N7-N8. The overall age from both primary and secondary data, the Semilir Formation is N4-N16, with a time gap of N7-N8.